Accounting for local impacts of photovoltaic farms: two stated preferences approaches - Botelho, Anabela (2016)
Renewable energy sources for electricity generation are unequivocally more environmentally friendly than the traditional sources, but are not impact-free. Given the potential for solar photovoltaic energy to contribute to the energy mix in some countries, it is timely to carefully consider the potential environmental costs of operation of photovoltaic farms, which are experienced by the local population, while the general benefits accrue to all. These adverse impacts should be identified and acknowledged. This paper proposes and applies economic valuation methods to estimate the value of those environmental impacts. We apply the contingent valuation method to a sample of local residents close to three selected photovoltaic farms in Portugal. We design a discrete choice experiment to elicit the valuation of specific adverse impacts of electricity generation through photovoltaic energy by national residents. Our results show that the value elicited in the vicinity of the photovoltaic farms is non-negligible and national residents value positively and differently the different adverse local impacts. Both of these estimates, in conjunction or independently, can be used to fully account for this often neglected cost of solar energy. The asymmetric equity implications of photovoltaic projects should not be neglected when deciding their construction and location.